Circadian rhythms - Young, Michael W., 1949- (Methods in enzymology, 2005)
The critically acclaimed laboratory standard, Methods in Enzymology, is one of the most highly respected publications in the field of biochemistry. Since 1955, each volume has been eagerly awaited, frequently consulted, and praised by researchers and reviewers alike. The series contains much material still relevant today - truly an essential publication for researchers in all fields of life sciences. Circadian Rhythms contains an extensive discussion of genetic and biochemical aspects of circadian rhythms. In this volume organisms such as neurospora, bacteria, drosophila, arabidopsis and mammals are covered. Included are methods in genetics, transcriptional and post-transcriptional regulation, tissue culture, and populations are discussed in detail. * One of the most highly respected publications in the field of biochemistry since 1955 * Frequently consulted, and praised by researchers and reviewers alike * Truly an essential publication for anyone in any field of the life sciences.